LEXICOGRAPHY: SYNONYMS, ANTONYMS AND HOMONYMS IN ENGLISH - Norpulatov Dilshod (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT: Lexical relations such as homonymy, synonymy, and antonymy constitute the backbone of meaning organization in English and many other languages. Homonyms  are  words  that share  either  sound, spelling, or  both  while diverging in meaning  and  grammatical  distribution.  They  are  traditionally  divided  into  three primary types: (1) homonyms proper, which are identical in both pronunciation and orthography  (bank  meaning  a  riverbank  versus  a  financial  institution);  (2) homophones, which share pronunciation but differ in spelling (knight versus night); and (3) homographs, which share spelling but differ in pronunciation or sense (bow [the front of a ship] versus bow [to bend]. Further subclassifications consider part-of-speech alignment—lexical  homonyms  belong  to  the  same  grammatical  category,  whereas lexico-grammatical homonyms cross categories (left the direction versus left the past of leave)—and paradigm overlap, distinguishing full homonyms whose inflectional paradigms match (match → matches) from partial homonyms whose paradigms only partially coincide (lie → lying vs. lied). Synonymy involves distinct lexical items that convey overlapping denotative content but differ in distributional frequency, stylistic register, intensity, duration, or contextual suitability.